Sistema Informático que permita estimular la capacidad y estimar el desarrollo mental de los alumnos de CEPRODIS de la ciudad de Loja basado en sistemas expertos. - Carrión Carrión, Marco Enrique (2012)
To achieve this thesis I present the performance of an expert system called DISSOFT, in which was applied to the ICONIX development methodology and has been developing based on the needs of CEPRODIS Center (Protection Center Disability) taken account of the lack of systems to assist the analysis of perceptions of psychomotor skills and behavior of students in CEPRODIS, all in support of everyday activities inside the Orientation Area taking into account the behavioral test are presented students to reach an accurate conclusion. Using the ICONIX methodology fits perfectly with what I need to get to the realization of my thesis project and thus helps me to necessarily end with the main objective and the time I have for the completion of it, so pattern that taking the steps and emphasizing that the paradigm is object-oriented development I focused mainly on the Raven test to get an easy way to students, the Raven test is a test relatively easy to understand but not is verbal may prescribe a lot about the person doing it, so you can reach only one conclusion absolutely. But I hope it's more pleasing to the community's thesis presented below